2013
DOI: 10.11118/actaun201361051451
|View full text |Cite
|
Sign up to set email alerts
|

Landscape dynamics in the Brno's surrounding between 2001 and 2011

Abstract: VAVROUCHOVÁ HANA, TOMAN FRANTIŠEK: Landscape dynamics in the Brno's surrounding between

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…The typical symptoms of the suburbanization process are an increase in built-up areas and a decrease in arable land. Attention has been paid to this by many researchers, including Vavrochova and Toman [14], Antrop [1], Mosammam et al in Qom city [32] and Hualou et al in Chinese cities [33]. The above research carried out in rural areas of the Upper Silesia-Zagłębie Metropolis also confirmed this, but with some differences.…”
Section: Inner Suburbanization As the Main Process Of Transformation ...mentioning
confidence: 68%
See 2 more Smart Citations
“…The typical symptoms of the suburbanization process are an increase in built-up areas and a decrease in arable land. Attention has been paid to this by many researchers, including Vavrochova and Toman [14], Antrop [1], Mosammam et al in Qom city [32] and Hualou et al in Chinese cities [33]. The above research carried out in rural areas of the Upper Silesia-Zagłębie Metropolis also confirmed this, but with some differences.…”
Section: Inner Suburbanization As the Main Process Of Transformation ...mentioning
confidence: 68%
“…They were also analyzed in terms of the intensity of the suburbanization processes, which is indicated, among other things, by the increase in the type of residential area and the decrease in arable land [1]. According to the guidelines of Antrop [1], as well as Vavruochova and Toman [14], the indicators of the suburbanization process were considered to be an increase in urban fabric (1.1) and a decrease in arable land (2.1). In addition, due to the location in the area of the former industrial district and in the area of influence of the Katowice Special Industrial Zone, the increase in industrial, commercial and transport units (1.2) was also analyzed as a suburbanization indicator.…”
Section: Research Procedures and Data Sourcesmentioning
confidence: 99%
See 1 more Smart Citation
“…3). In the second step of the study, the ICh index of landscape change was calculated, which determines the percentage of land that underwent transformations (Vavrouchová, Toman, 2013). On this basis, it was determined how much transformation was taking place, and the compilation of the results of the index in time sequences made it possible to study the dynamics of landscape transformation.…”
Section: Methodsmentioning
confidence: 99%